Complementary-Alternative Medicine in Rheumatoid Arthritis - Demirhan Dıraçoğlu, (Archives of Rheumatology, 2007)
Diagnostic, therapeutic and preventive applications that contribute to general medical techniques and conceptually not included in classical medicine, are called Complementary-Alternative Medicine (CAM). Recently, CAM has been used in the treatment and rehabilitation of rheumatoid arthritis (RA) adjunct to classical medical techniques. In this article, the role of CAM techniques in RA treatment and rehabilitation in the light of objective scientific data was discussed. More frequently preferred CAM techniques in RA patients are herbal medicine, dietary supplements, special diets, tai chi, yoga, acupuncture, homeopathy, relaxation techniques, manipulation, massage, spritual healing and meditation. According to statistical data CAM applications are accepted by the patients as a back up to modern medical techniques rather than an alternative to them. It was observed in some controlled studies that CAM techniques, which are special diets, supplements, herbal medicine and homeopathy, have positive effects on RA. But there is still a need for more well designed studies for each specific CAM technique in order to get scientific proof of their value, and thus their use in routine daily practice. (Rheumatism 2007; 22: 24-30)